Analysis of Failure to Pay Education Fee Receivables at XYZ Institution - Rasyadan, Resa; Wibowo, Buddi (Syntax Corporation, 2024)
The XYZ Institution/Agency, as a governmental institution, has the obligation to resolve debts resulting from financial losses. This study aims to analyze the influence of demographic, financing, and educational institution characteristics on the default of educational debt/student loan (State Compensation Claim for Breach of Service Agreement) at the XYZ Agency. To achieve this objective, the study utilizes data on debtors from 1983 to 2022 at the XYZ Agency and employs binary logistic regression analysis. The results of this study indicate that age and receivable value significantly affect the quality of the debtor's receivables. Specifically, debtors who are over 26 years old and have receivable values above IDR 200,000,000 are more likely to default. In contrast, gender and campus status do not significantly impact the default rates. These findings are expected to provide insights for the XYZ Agency in improving the management of state debts, particularly educational debts, and contribute to the development of policies related to debt management in the public sector. This study also provides a comprehensive overview of the variables influencing the default of educational debts at the XYZ Agency, with a focus on the State Compensation Claim (TGR) process at the XYZ Agency.